2020
DOI: 10.1093/glycob/cwaa023
|View full text |Cite
|
Sign up to set email alerts
|

Functional exploration of the GH29 fucosidase family

Abstract: The deoxy sugar l-fucose is frequently found as a glycan constituent on and outside living cells, and in mammals it is involved in a wide range of biological processes including leukocyte trafficking, histo-blood group antigenicity and antibody effector functions. The manipulation of fucose levels in those biomedically important systems may provide novel insights and therapeutic leads. However, despite the large established sequence diversity of natural fucosidases, so far, very few enzymes have been character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…The highly diverse gut microbiota expresses different enzymes with similar mucus-degrading capabilities. Available genomes from gut microbiota members indicated that a majority of the organisms have the capability to cleave, and catabolize, at least one of the mucin O-glycan monosaccharides [13,18], and more data are becoming available on the characterization of mucin-degrading CAZymes from gut mucosal microbes [13,[19][20][21][22]. For example, the large and diverse glycoside hydrolase 16 (GH16) family were recently characterized as endoacting enzymes and were described to target the polyLacNAc structures within the oligosaccharide side chains of mucins.…”
Section: Microbial Adaptation To Mucin Glycansmentioning
confidence: 99%
“…The highly diverse gut microbiota expresses different enzymes with similar mucus-degrading capabilities. Available genomes from gut microbiota members indicated that a majority of the organisms have the capability to cleave, and catabolize, at least one of the mucin O-glycan monosaccharides [13,18], and more data are becoming available on the characterization of mucin-degrading CAZymes from gut mucosal microbes [13,[19][20][21][22]. For example, the large and diverse glycoside hydrolase 16 (GH16) family were recently characterized as endoacting enzymes and were described to target the polyLacNAc structures within the oligosaccharide side chains of mucins.…”
Section: Microbial Adaptation To Mucin Glycansmentioning
confidence: 99%
“…GH29 is the largest fucosidase family, with more than 5000 entries in the CAZy database, but only 34 fucosidases have been characterized. They act through a retaining mechanism and have a broad substrate specificity . The donor substrate is recognized through the nucleophilic amino acid of the enzyme to form the intermediate fucosyl-enzyme, which is not stable and can be hydrolyzed in the presence of water.…”
Section: Enzymatic Synthesis Of 2′-flmentioning
confidence: 99%
“…This database classifies fucosidases into three families (GH29, GH95, and GH151) according to their catalytic structures. GH29 fucosidases act through a retaining mechanism and have a broader substrate specificity, including hydrolysis of Fuc-α1,3/4/6 linkages [15]. Moreover, family GH29 fucosidases have been subclassified into two subfamilies.…”
Section: Introductionmentioning
confidence: 99%